Pengaruh Gaya Kepemimpinan Demokratis Dan Motivasi Kerja Terhadap Kinerja Karyawan pada Restaurant Suji Suan Cai-Yu Pondok Indah Mall- Jakarta Selatan - Fajrianti, Nurul (JURNAL EKONOMI, BISNIS DAN HUMANIORA, 2024)
This research intends to test, study and analyze the influence of democratic leadership style and work motivation on employee performance at Suji Suan Cai-Yu Restaurant. The hypothesis tested is Democratic Leadership Style and Work Motivation on the Performance of Suji Suan Cai-Yu Restaurant Employees. The population of this research is all employees who work at Restaurant Suji Suan Cai Yu Pondok Indah Mall. The sample that will be used by researchers is 48 respondents. (a) Based on the calculation results, Democratic Leadership Style (X1) influences Employee Performance (Y) at Suji Suan Cai-Yu Restaurant. This is proven by the hypothesis test value tcount > ttable or (2.261 > 2.014) with a significant level of (0.029 < 0.05). Thus Ho1 is rejected and Ha1 is accepted. (b) Work Motivation (X2) has a positive and significant effect on Employee Performance (Y) at Suji Suan Cai-Yu Restaurant. This is proven by the hypothesis test tcount > ttable or (2.947 > 2.014), this is confirmed by <sig.0.05 or (0.005 <0.05). Thus, Ho1 is rejected, Ha2 is accepted. (c) Democratic Leadership Style (X1) and Work Motivation (X2) have a positive and significant effect simultaneously on Employee Performance (Y) at Restaurant Suji Suan Cai-Yu. This is proven by hypothesis testing, the value Fcount > Ftable or (31.049 > 2.81). With a significant value level of 0.000 <0.05. And the coefficient of determination R² is 0.561 or a simultaneous influence contribution of 56.1%. Thus Ho3 is rejected and Ha3 is accepted.